2020
DOI: 10.1002/star.202000112
|View full text |Cite
|
Sign up to set email alerts
|

Infrared Radiation: Impact on Physicochemical and Functional Characteristics of Grain Starch

Abstract: Infrared (IR) is a highly efficient and energy‐saving technology known for uniform heating, less heating time, and high energy transfer rate to improve food product quality and safety. IR technology has many applications, including drying and dehydration, enzyme inactivation, pathogen inactivation, and other miscellaneous uses such as roasting, frying, and broiling. However, the effect of IR radiation on the overall behavior of the grain and its components has not received much attention. This review focuses o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 45 publications
0
10
0
Order By: Relevance
“…The higher porosity in GBR‐I and PGBR‐I also contributed to soft texture of GBR‐I and PGBR‐I. In addition, Semwal and Meera (2020) reported that the IR energy could alter the starch structure, resulting in changes in functional properties including higher water absorption and greater swelling capacity.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The higher porosity in GBR‐I and PGBR‐I also contributed to soft texture of GBR‐I and PGBR‐I. In addition, Semwal and Meera (2020) reported that the IR energy could alter the starch structure, resulting in changes in functional properties including higher water absorption and greater swelling capacity.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, IR caused the rice grains to be more porous, thus increasing the extractability of GABA. Specifically, the advantages of IR heating include high heat transfer efficiency, uniform heat penetration into the rice grain, and short processing time (Aboud et al., 2019; Semwal & Meera, 2020). The shorter drying time helps to preserve GABA in the rice grain.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In most cases, crushers used in practice for grinding grain are relatively inexpensive, but their use does not solve the problem of increasing the nutritional value of feed. Infrared radiation improves the digestibility and nutritional properties of grain forage (Semwal & Meera, 2020). However, the energy costs of infrared emitters are high and amount to at least 0.33 kW h/kg.…”
Section: Introductionmentioning
confidence: 99%